As Bignoniaceae do Parque Estadual do Guartelá, Tibagi, Estado do Paraná, Brasil1 - Monzoli, João Victor Longhi [UNESP] (2021)
Bignoniaceae family gather 82 genera and about 860 species distributed mainly by the neotropical region, and Brazil has the occurrence of approximately 33 genera and 416 species. Evaluating that Parque Estadual do Guartelá represents an important remnant of the Campos Gerais and that there are few studies on the Bignoniceae in the southern region of the country, this work aimed to contribute to the characterization of its flora through the monograph for the Bignoniaceae occurring in the area. The collections were made along trails and roads, as well as in forays into fields and forests, during 12 months. Adenocalymma, Amphilophium, Anemopaegma, Bignonia, Dolichandra, Fridericia, Handroanthus, Jacaranda, Mansoa, Pyrostegia, Tabebuia e Tynanthus were the registered genera, totaling 18 species.